2018
DOI: 10.1155/2018/9724176
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, Alcohol Consumption, and Illegal Substance Abuse among Adolescents in Sri Lanka: Results from Sri Lankan Global School-Based Health Survey 2016

Abstract: Background. Adolescence is defined by the World Health Organization (WHO) as “the transition period from childhood to adulthood”. Increases in autonomy during this period, willingness to experiment, and peer influence create an environment of taking high-risk decisions influencing adolescent health, such as substance abuse and smoking. The current study was conducted to estimate the prevalence of smoking, alcohol consumption, and illegal substance abuse and their determinants on in-school adolescents using dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 16 publications
2
18
4
Order By: Relevance
“…e magnitude of the prevalence lifetime and current cigarettes smoking were almost similar 4.8% and 4.5%, respectively. is finding is lower than a study in Woldia Town 23.5% [21] and a study in Addis Ababa University students 9% [15], and a study in Rift Valley University 18.4% [37], but higher than a study in Sri Lanka 2.3% [35]. is small prevalence in this study may be attributed to underreporting due to self-reporting or it might be because of the differences in study setting and population.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…e magnitude of the prevalence lifetime and current cigarettes smoking were almost similar 4.8% and 4.5%, respectively. is finding is lower than a study in Woldia Town 23.5% [21] and a study in Addis Ababa University students 9% [15], and a study in Rift Valley University 18.4% [37], but higher than a study in Sri Lanka 2.3% [35]. is small prevalence in this study may be attributed to underreporting due to self-reporting or it might be because of the differences in study setting and population.…”
Section: Discussioncontrasting
confidence: 87%
“…In the current study, the prevalence of a lifetime and current alcohol use was 42.16% and 26.1%, which is congruent with a study in Uganda [38] that reported 26.8% of current alcohol users and is lower than a study done in Woreta Town [22] that reported 40.9% and 59% prevalence of current and life time prevalence of alcohol use, while a similar study conducted in Sri Lanka reported a lower prevalence of alcohol uses (3.4%) [35]. e current and lifetime prevalence of khat chewing was 16.6% and 17.8%.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Out of these, factors related to the domains of lack of parental involvement, presence of violence and not engaging in sports activities were detected as independently associated with the psycho-social attributes. Even if the substance-use did not yield direct signi cant associations with these four attributes, these are well known to be associated with factors that increase their likelihood with reference to observations of the same study population (11,32). This highlights the need of a comprehensive package addressing the web of causation of these related outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these legal measures, there has been an increasing tendency among people to use illicit drugs such as opioids and cannabis. A school based health survey in Sri Lanka in 2016 reported that the prevalence of alcohol, smoking, smokeless tobacco and substance abuse was 3.4%, 3.6%, 2.3% and 2.7% respectively (5). In 2016, the average street price of a kilogram of cannabis and opium was rupees 22,000 and rupees 1.5 million respectively (6).…”
Section: Introductionmentioning
confidence: 99%